Gastrointestinal Perforation Due to Gastrointestinal Stromal Tumour (GIST) In Small Intestine-A Case Report (Journal of Surgical Sciences, 2019)
Gastrointestinal stromal tumors (GISTs) is a mesenchymal tumor of GI tract. Now a daysdiagnosis of GISTs is more frequent then previous due to advance diagnostic tool. GISTsusually present with abdominal mass and GI bleeding but it may also present with manyunusual pattern like obstruction, perforation. Perforation of GISTs is extremely rare presentation.We report a case of pneumoperitoneum due to perforation of small intestinal GIST.Emergency laparotomy followed by resection and end to end anastomosis was done. Aftersurgical treatment lmatinibmesylate was given for prevention of early recurrence.Journal of Surgical Sciences (2016) Vol. 20 (2) :65-67